Digitalisasi Layanan Pertanahan di Badan Pertanahan Nasional Kota Surabaya dalam Upaya Mencegah Mafia Tanah - Syarifudin Prasetyo, Afif; Supriyo, Agus (DOKTRINA: JOURNAL OF LAW, 2025)
This study aims to analyze efforts to digitize land services in overcoming land mafia practices in the city of Surabaya, with a focus on the implementation of a technology-based land information system. The research method used is normative juridical with a statute approach and a historical approach. The statutory approach is used to examine various regulations governing the digitization of land services in Indonesia such as the Agrarian Law and its implementing regulations. The results found that digitization is considered a solution to increase transparency, accountability, and efficiency of land services, which are expected to reduce the opportunity for data manipulation or fraud. The implementation of an electronic land registration system (e-land registry) and online application-based services in the city of Surabaya provides easy access to information for the public and accelerates the land administration process. Some challenges such as the lack of digital literacy among the public and limited technological infrastructure. so that collaborative efforts between the government, the community and the private sector to continue to develop a more inclusive and effective digital system to overcome land mafia in the future.